Effect of sodium on methanogens in a two-stage anaerobic system - Xiao, Keke (2022)
This study evaluated the effects of sodium on anaerobic biomass from the second-stage reactor of a two-stage anaerobic digester. The results indicated that methanogens showed a rela-tively high sodium tolerance of 2.4 g Na+ L−1 . Microbial community analysis showed that viable Methanomicrobiales was the most abundant population by a combined propidium monoazide cross-linking quantitative polymerase chain reaction technique. There was a population shift towards higher abundance of Thermotoga (0.02%), Clostridium (2.50%) and Methanoculleus (13.80%). Biomass activity in relation to increased sodium concentrations was investigated with the adenosine triphos-phate test coupled with extracellular polymeric substances measurement. The results showed biomass activity decreased from 33 to 16 µg g−1 volatile suspended solids as sodium concentrations increased from 1.3 to 9.1 g Na+ L−1 . Higher EPS production, particularly a greater predominance of carbo-hydrates, was stimulated by higher sodium concentrations. This study provides insights into the superiority of sodium tolerance of two-stage anaerobic digester in compared with a single-stage anaerobic system.